IKTIOFAUNA AIR TAWAR BEBERAPA DANAU DAN SUNGAI INLETNYA DI PROVINSI SULAWESI TENGAH, INDONESIA - Muh. Herjayanto; Abdul Gani; Yeldi S Adel; Novian Suhendra (Jurusan Akuakultur, Universitas Bangka Belitung, 2019)
Sulawesi Tengah Province (Sulteng) is in the Wallacea region wich have endemic fish. In addition, the government has also introduced fish for the welfare of community. So far the records of freshwater fish in Sulteng have not been well summarized. Therefore, we explore the results of previous studies fish species in 11 lakes and their inlet rivers in Sulteng. The lake (L) is L. Bolano (Bolanosau), L. Lindu, L. Poso, L. Rano, L. Rano Kodi and L. Rano Bae, L. Sibili, L. Talaga (Dampelas), L. Kalimpa’a (Tambing), L. Tiu and L. Wanga. In addition, we also observed fish in seven lakes between 2012-2019. Fishing uses cast net, seine net, gillnet, and hook and line. Summary and observation result showed that there were 18 families and 27 genera of fish in 11 lake and their inlet rivers in Sulteng. Then there are 15 endemic species in 3 habitats (Lindu, Poso and Tiu), namely Adrianichthys 4 species, Oryzias 6 species, Mugilogobius 2 species and Nomorhamphus 3 species. Introduced fish as many as 23 species, Oreochromis niloticus the most found (8 lakes). Lake Poso (30 species) has the most fish species. Utilization of fish in 11 lake as consumption fish and ornamental fish. Especially for endemic fish, in situ (habitat) and / or ex situ (aquaculture) conservation needs to be carried out in order to remain sustainable. Through aquaculture, the breeding of endemic species that have the potential as ornamental fish and/or consumption can be avoided from exploitation (overfishing) in nature.